1982
DOI: 10.1152/ajpheart.1982.243.5.h761
|View full text |Cite
|
Sign up to set email alerts
|

Right and left ventricular oxygen metabolism in open-chest dogs

Abstract: A comparison of blood flow and myocardial O2 consumption (MVO2) in the right and left ventricles was made in 21 open-chest dogs. Simultaneous measurements were made of left anterior descending (LAD) and right coronary arterial blood flow and of O2 saturation in the coronary sinus and in from one to four anterior cardiac veins. Blood flow was greater in the LAD than in the right coronary artery, 87 +/- 5 vs. 46 +/- 3 ml.min-1.100 g-1. Similarly, the O2 saturation was 51 +/- 3% in the anterior cardiac veins and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
4

Year Published

1990
1990
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 0 publications
2
42
0
4
Order By: Relevance
“…Moreover, our results agree nicely with animal studies showing that dysfunctional RV ischemic myocardium consists predominantly of viable or only modestly necrotic tissue, 7,8 indicating that the RV is more resistant to ischemic injury than the LV. This can be attributed to a more favorable oxygen demand/supply profile for the RV, as follows: (1) by facing lower stroke work 23 ; (2) by extracting less oxygen at rest and thereby having greater oxygen reserve during stress 23 ; and (3) by resulting in more efficient circulation due to high systolic/diastolic flow ratio and protective anatomic collaterals from the left coronary system. 24,25 Although LGE imaging is an established technique for depicting LV myocardial necrosis and/or fibrosis, 19,20 this technique has been much less validated for RV MI assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our results agree nicely with animal studies showing that dysfunctional RV ischemic myocardium consists predominantly of viable or only modestly necrotic tissue, 7,8 indicating that the RV is more resistant to ischemic injury than the LV. This can be attributed to a more favorable oxygen demand/supply profile for the RV, as follows: (1) by facing lower stroke work 23 ; (2) by extracting less oxygen at rest and thereby having greater oxygen reserve during stress 23 ; and (3) by resulting in more efficient circulation due to high systolic/diastolic flow ratio and protective anatomic collaterals from the left coronary system. 24,25 Although LGE imaging is an established technique for depicting LV myocardial necrosis and/or fibrosis, 19,20 this technique has been much less validated for RV MI assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Since an increase in demand for coronary flow reflects an increase in myocardial oxygen consumption, it is suggested that the increase in afterload for the right ventricle by pulmonary stenosis augmented oxygen consumption of the ventricular free wall through an increase in right ventricular wall stress caused by increases in preload and afterload for the wall. Kusachi et al (1982) showed that constriction of the pulmonary artery increases myocardial oxygen consumption of the right ventricle by both augmented oxygen extraction and a rise in right coronary blood flow. Thus, more prominent deterioration of right ventricular wall movement at ischemia in right ventricular pressure overload, compared to the condition with normal pulmonary circulation, appeared to be mainly due to the increase in ischemic change of the right ventricular wall muscle, although the increase in afterload for the right ventricular wall could mechanically depress the right ventricular wall motion.…”
Section: Discussionmentioning
confidence: 99%
“…Based on canine studies, normal RV OEF has been estimated as 45-50%, 20,21 indicating that the RV has a substantially higher O 2 extraction reserve than the left heart (OEF values are 60 -80% in healthy men). 4,5 Additionally, Hart et al 21 demonstrated that during heavy exercise, RV O 2 utilization increases initially by maximizing OEF before coronary reserve is mobilized.…”
Section: Wong Et Al Inefficient O 2 Use By Failing Right Heart In Pahmentioning
confidence: 99%